The effect of motion on wind tunnel drag measurement for athletes - D'Auteuil, A.; Larose, G. L.; Zan, S. J. (Procedia Engineering, 2012)
To optimize the reduction of the drag area coefficient of a speed skater, mannequins in static positions wearing suits were tested in the NRC 2m x 3m Wind Tunnel to find the lowest drag for a given range of speeds. The results obtained from this study can only be interpreted and applied to a speed skater if the aerodynamic drag coefficient is not affected significantly by the motion of the skater. It has been assumed that, for a representative cadence or frequency of oscillation of a speed skater lower than 1 Hz which is representative of the motion in a race, the aerodynamics could be considered quasi-stationary. The quasi-steady state is defined by the flow that developed around the body and the wake both governing the aerodynamic drag compared to the contribution of the low frequency of oscillation of the body. To verify this hypothesis and to determine to what extent the quasi-steady assumption is valid for a human body in a speed skating position, a study was carried out in a wind tunnel using a moving life-size mannequin. A mechanism was devised so that a mannequin in a sidepush position could be oscillated to mimic the sinusoidal path of a speed skater. The amplitude of motion was kept constant and the frequencies of oscillation and wind speeds were changed to cover the equivalent of 500 m to 10,000 m races. The experiments have revealed that the variations of the drag area coefficient with wind speed were similar for static positions and for cases where the mannequin was oscillating at frequencies lower than 0.67 Hz or for a period of rotation of 1.5 s. The drag reduction occurred at the same wind speeds for the static and dynamic cases. This paper presents details of the experiments and a summary of the main findings.